Transcatheter reduction in size of large undesirable fenestrations following extracardiac conduit Fontan surgery with off-label use of Occlutech atrial flow regulator - Bhushan Shivaji Sonawane; Kothandam Sivakumar (Wolters Kluwer Medknow Publications, 2020)
Fontan surgery streamlines the systemic venous return through the pulmonary circulation before filling the systemic ventricle in univentricular hearts. The venous congestion leads to effusions, lowers cardiac output, and affects organ perfusion. Fenestrations in the Fontan circuit improve forward flow through the ventricles, lower venous pressures, and reduce perioperative morbidity. When large fenestrations cause profound hypoxia and effort intolerance, there are no current techniques to reduce their size. Atrial flow regulators with a predetermined orifice were used off-label in three borderline patients with large undesirable fenestrations following extracardiac conduit Fontan surgeries. This resulted in improved oxygenation without marked elevation of venous pressures, while retaining the patency of the decompressive fenestration.